Kamu sektörü borçlanma gereği ve açıklarının finansmanı için uygulanan borçlanma yöntemleri - Önenç, C. Cem (My University, 2001)
Genel olarak ülkemiz dışa kapalı ekonomi döneminde (1963-1980), kamu harcamalarının yatırım ve dış fazlanın toplamından oluşan gayrısafi ulusal tasarruflar üzerinde ciddi bir etkide bulunmadığı anlaşılmaktadır. Ancak, toplam kamu harcamalarının tüketim ve yatırım olarak ayrıştırılması durumunda, kamu yatırımlarının GSYİH'ya oranında meydana gelen artışların, bu dönemde dış dengede bire-birlik bozulmalara yol açtığı dikkati çekmektedir. Başka bir değişle, dışa kapalı dönemde kamu yatırımlarında meydana gelen artışlar net dış yükümlülük yaratılarak gerçekleştirilmiştir. 1987 sonrası dönemde ise kamu harcamalarının ekonomideki diğer makro büyüklükler üzerindeki bozucu etkisinin arttığı gözlemlenmektedir. 1987-1995 arasındaki dönemde kamu harcamalarının GSYİH'ya oranında meydana gelen artışlar, gayrisafi ulusal tasarrufları (yatırım artı dış fazla) azaltıcı bir etkide bulunmaktadır. Bu dönemde gerek kamu tüketim harcamalarının, gerekse kamu yatırım harcamalarının net dış yükümlülük yaratıcı bir nitelik kazandığı anlaşılmaktadır. Pek çok araştırmanın sonucu, kamu tüketim harcamalarının 'investment crowding out' ile birlikte ve daha çok 'dış denge bozucu' yani net dış yükümlülük arttırıcı bir karakteri olduğunu göstermektedir. Dahası kamu tüketim harcamalarına gelen şok artışlar geçici olmamakta ve kalıcı bir özellik göstermektedir. Aynı zamanda özel tüketim harcamalarında meydana gelebilecek kalıcı azalmaların, toplam tasarrufları olumlu yönde etkileyeceği açıktır. Harcamalarında belirli bir disiplini sağlayamayan kamu kesimi., harcama artışlarını karşılayabilecek bir gelir artışı gerçekleştirememiştir. Bunun sonucunda Kamu Kesimi Borçlanma Gereği'nin GSYİH'ya oranı, (KKBGO), sürekli bir artış içerisindedir. Ekonomide bir dizi önlemin alındığı 1994 yılı içerisinde bu oranda uzun yıllardan bu yana bir azalma gözlenmiştir. Ancak bu göreceli düzelmenin geçici olduğu anlaşılmaktadır. Sözkonusu yıl toplam kamu yatırımlarının GSYİH'ya oranı, tarihinde görülmemiş boyutlarda azalarak yüzde 3.4'e düşmüştür. Yatırımlar da bir önceki yıla göre meydana gelen 4.1 puanlık azalmaya karşın KKBGO'da gerçekleşen azalmanın 3.1 puanda kalması ilginçtir. Kamu açıkları veri iken açık finansman yöntemleri oldukça kısıtlıdır: · Para Basmak · İç Borç Bulmak · Dış Borç Bulmak Kamu otoritesi her üç finansman biçimi ile ilgili olarak iktisadi dinamiklerin dayattığı zorunluklar dışında herhangi bir kısıt altında bulunmamaktadır. Toplam dış borçların kamu ve özel olarak ayrıştırılmasında özel kesimin dış borçlanmada belirli bir esnekliğe ahip olduğu, kamu borçlarının ise sürekli bir artış içerisinde olduğu dikkati çekmektedir. Özel kesim borçlanmasının da üretken yatırmlardan çok yine kamu açıklarının finansmanına yöneldiği bilinmektedir. Kamu Kesimi toplam iç borçlarının sadece bir kısmını oluşturan hazine tarafından açıklanan toplam tahvil ve bono stokunun da zaman içerisinde hızla yükseldiği gözükmektedir. Kimi zaman toplam borçların GSYİH'ya oranı gösterilerek kamu borçlarının bir sorun teşkil etmediği öne sürülmektedir. Bu tür argümanlar, Türkiye'de toplam borç stokunun ortalama vadesinde meydana gelen azalmayı ve finansal piyasaların sığlığını göz ardı etmektedir. İzlenen iktisat politikalarına güvensizlikle birlikte borçların ortalama vadesi kısalırken, çok yüksek reel faizlerle borçlanabilmek ancak mümkün olabilmektedir. Bu ise, faiz dışı bütçe fazla verse bile toplam borçların GSYİH'ya oranının sürekli olarak artmasına neden olmaktadır. Faiz konusuna gelince genellikle faizin bir sebep oılduğu düşünülür. Esasında faiz bir sonuçtur. Faizi tasarruf arzı ile talebi oluşturur. Son 5 yıla kadar Türkiye'de kamu sektörünün fon talebi GSMH oranı olarak küçüktü. Yani kamunun fon talebi göreli olarak azdı. Ancak bu dönem boyunca faizlerin hem nominal hem de reel olarak yukarı gittiği gözlendi. Çünkü ülkemizde fon arzı kıttı, yani tasarruf birikimi yoktu. Bu nedenle faiz enflasyonun oldukça üzerinde seyretti. Üstelik kötü siyasi yönetiminin doğal sonucu olarak kötü ekonomik yönetim sonucunda yerleşikler Türk Lirası tutmayı bırakıp dövize yöneldi. Bu durum risk algılamasını arttırdığından dolayı faiz enflasyonun oldukça üstüne çıktı. Bu arada yurt dışından Türkiye'ye para girişi de yaşandı. Sıcak Para adı altında mevcut arbitrajdan yararlanmaya çalışan bu paranın miktarının çok olduğu düşünüldü ancak bu para da son derece sınırlıydı çünkü enflasyonun oldukça üstünde seyreden faizlerin yanısıra siyasi oynaklık Türkiye'yi yatırım açısından son derece riskli bir duruma sokmuştu. Bu nedenlerin toplu sonucu faizler uzunca bir süre yüksek kaldı. Temel olarak enflasyonu arttıran ve sürekliliğini sağlayan kamu kurumları bütçe açıkları. Bu kurumlar çok mu verimsiz? Belki daha verimli kullanım şansına sahip olunabilirdi. Ancak uzunca bir dönem boyunca siyasetin verimsizliği bu durumu oluşturdu diyebiliriz. Yani gerçekten verimsizlik kurumlarda mı yoksa bunları yönlendiren insanlarda mı? Bütçe açıklarının kamu zamlarına zam yapılarak finanse edilmesi enflasyonu azdıran en önemli faktör olarak önümüze çıkıyor. Yani kısacası enflasyonun kendisi başlı başına bir finansman metodu haline getirilmiş bulunuyor. Enflasyon arttıkça faiz, faiz yukarı gittikçe risklilik artıyor. Ve tabii sarmal devam ederek risklilik arttığından faiz daha da artıyor. Bu durumda çözüm esasında çok uzak değil. Örneğin ilk akla gelen vergi toplamak; ancak bunun için öncelikle çaba gerekli bordrolu çalışanlar üzerine yüksek vergi yükü getirmektense (üstelik sosyal adaletin de bir gereği olarak) vergi tabanı genişletilmeli. Tabii bu yapılırken çok fazla kavga çıkarmaya da gerek yok. İkinci olarak kamu harcamalarının düşürülmesi; ancak bu da son 10 yıllık dönemde gözlendiği kadarıyla, sık seçimin olduğu bir ortamda çok da mümkün değil çünkü oy satın almak amacıyla kamu harcamalarının yoğunlaşması gerek şart. Bu durumda IMF ile yapılan anlaşmalara bağımlılık çok yadırganmamalı. 2000 yılında konsolide bütçe yüzde 12,1 açık verirken, tüm kamu birimleri bir arada düşünüldüğünde toplam bütçe açığı GSMH oranı olarak yüzde 23,3 rakamına ulaşmış durumda. Bu sonuca ulaşırken değişkenlerin tanımlanması gerekiyor. 1999 yılında açığın büyük kısmının tarım desteklemesi sonucunda kamu bankalarında oluşan görev zararları ve KİT bütçelerindeki dengesizliklerden kaynaklandığı gözleniyor. Bütçe dışındaki fonların ve mahalli idarelerin de önemli ölçüde açık verdiğini, sosyal güvenlik kuruluşlarının açıklarının ise peşinen genel bütçeye aktarılması nedeni ile küçük gözüktüğünü ama en önemlisi konsolide bütçenin faiz dışı fazla verdiğini belirtmek gerekiyor. Sonuçta kamu açığı analiz edilecekse, konsolide bütçenin ötesinde diğer kamu birimlerinin açıklarının da göz önüne alınması gerekmektedir. Bu sonuca bizleri en güvenilir şekilde Kamu Kesimi Borçlanma Gereği götürmektedir. Son yıllardaki tüm kamu bütçelerinden faiz arındırılarak bir değerlendirme yapılırsa ortaya; konsolide bütçenin, sosyal güvenlik açıklarının da içine aktarılmış olmasına rağmen fazla vermekte olduğu sonucu çıkıyor. Yani esas temel açık konsolide bütçe dışındaki kalemlerden geliyor. Üç temel açık kaynağı var: · Bütçe Dışı Fonların açıkları, · Kamu İktisadi Teşekkülleri açıkları, · Kamu Bankaları görev zararları, Tabii konsolide bütçe içine yerleştirilen sosyal güvenlik açıklarının da unutulmaması gerekiyor. Bu bahsedilen sorunların sayesinde iyice artan borç yükü dayanılmaz duruma gelince ardarda gelen iki kriz de eklenince Türkiye finansal piyasalarda küme düşen bir oyuncu durumuna düşmüştür. Sorunlar için çözümler üretilmiş ve üretilmeye devam edilecektir. Ancak Türkiye ekonomisi göstermiştir ki önündeki en büyük engel siyasi istikrarsızlıktır. Ne kadar mükemmel programlar yapılırsa yapılsın onun arkasında güçlü ve istikrarlı bir siyasi güç olmadığı sürece başarı şansı son derece düşük kalacaktır.

In Turkey, financial sector had not developed before 1980. After 1980, several reforms took place and the financial sector was enlarged. İn addition to the banking sector, which had been leader (even the sole player) in the financial sector, sevral new institutions were established; such as the Istanbul Stock Exchange Market (ISE), financial intermediaries, foreign exchange markets, Banklike Institutions (Islamic Banks), etc. However, afterall, desired developments could not be attained. The strength of the banking sector remained the same, and the financial sector had not deepen adequately. Public Sector Borrowing Requirement (PSBR) can be used to measure total deicit of the whole public sector. In detail PSBR is the difference between revenues and the expenditures of public sector. In this thesis, the definition of PSBR and methods of financing are examined. The sale of government securities through periodic auctions started in 1985. Banks and other authorized institutions were the buyers. Interest rates began to be determined in the market. Although the government was the sole seller , it did not have the monopoly power, since the liquidity need of public sector could not be decreased. It was shown that when the buyers observed the public sector's cash needs, then without establishing a collision they could invalidate the monopoly power of the government. Growing public sector deficits had to be financed by means of market and non - market mechanism was the tax exempt interest income on Treasury Bills and government bonds. The public sector reduces its present revenues when it gives subsidies to some sectors, and loses some of its future revenue by exempting some type of profits gained by investors on government securities. But, this fact, on the other hand, penalizes other the group who were not the beneficiaries of the subsidies since they had to pay the market cost which was higher than it would be if the public sector hadn't provide any subsidy. Moreover, newcomers receive no benefits and therefore they were operating with higher average costs. High rates of interest, on the one hand, increases savings and financial assets in the private sector, on the other hand, private sector decreases its demand for loans. Banks then use their increased funds by buying foreign exchange or decreasing their level of foreign liabilites or extending credits to the public sector. Public sector relatively less risky to lend especially when the interest rates are increasing. The private sector needs to accumulate sufficient net assets to outweigh the increase in the domestic currency value of the foreign liabilities, i. e. to compansate the exchange rate losses. If this was not sufficient, then real devaluation need to be complemented with an increase in real interest rate or monetary financing. There are two to things to be done to reduce the public sector deficit. Either the revenues were to increase or the expenditures were to decrease. In case of several other debtors, the decrease in expenditures were realized mainly by a reduction in public sector investments. In Turkey, there was a real decline in public investments, the reductin was not as severe as in other debtors. Public sector investment was not so much decreased due to the modernisation investments especially in telecomunication and electricity sectors. The personnel expenditures could be controlled until 1989 when the prime minister offered 100% increase in nominal wages, just before the 1991 elections. Due to populist policies before the 1991 elections, the control on wage rates were released. The nominal wage adjustments in the public sector drew the baseline for the collective bargaining in the private sector. Usally the wage increases in the private sector was parallel to the adjustments in the public sector. By this way, another resource transfer were realized: transfer of resources from the workers to the employers via the public budget. This kind of transfer aimed to compensate exporters and producers for increased import costs of inputs due to continous devaluations. Decreased production costs together with devaluation of the TL made exporters competitive in international markets. During the 1990s, economic crises began to affect the Turkish economy with increasing frequency. While external factors played a role, the main reasons for these crises were: (i) the development of an unsustainable domestic debt dynamic and (ii) the unhealthy structure of the financial sector, with particular problems caused by the state banks and by the failure to address structural problems. Unsustainable Domestic Debt Dynamic Between 1990 and 1999, the ratio of net public sector debt to GNP rose from 29% to 61%. The increase in the domestic debt stock is even more striking. In 1990, the ratio of net domestic debt to GNP had been 6%. By 1999, it had increased to 42%. (including the duty losses incurred by the state banks as a result of the assigned duties of supporting groups such as farmers and artisans). In the first half of the 1990s, the increase in debt stock resulted from the high primary deficits of the public sector. During the second half of the decade, the impact of high real interest rates became apparent. In the period 1990-1994, while the annual average ratio of the primary deficit to GNP was 4.5%, the operational public deficit including the real interest payments, discounted for inflation amounted to 8.3% of GNP. Between 1995 and 2000, the primary balance moved into a surplus averaging 0.1% of GNP. However, operational deficit averaged 5.8% of GNP. With these high public deficits and with the public sector making net repayments of external debt after 1994, the pressure grew on Turkey's financial markets. A combination of this pressure and the lack of depth of these financial markets opened the way to sustained high real interest rates. A further factor contributing to high real interest rates was the high and volatile inflation rate which increased the risk premium. Between 1992 and 1999, while the annual real growth rate averaged less than 4%, the real interest rate paid on domestic debt averaged 32%. Such levels of real interest rates increased the borrowing requirements of the public sector. All this created a vicious circle of debt and interest payments, pushing Turkey into an ever more difficult financial position. As evidenced by the increase in the debt stock, this situation clearly became unsustainable. As the impact of increasing real interest payments on the debt stock became evident in the second half of the 1990s, it became clear that, to solve the vicious circle of increasing debt and interest rates, a permanent improvement in the revenue and expenditure balance of the public sector was needed. In this respect, the following expenditure factors were important in the rise of the public deficit over the past decade; The increase in the unmonitored expenditures of extrabudgetary funds, revolving funds, and local administrations, together with expenditures by the state banks, in particular their duty losses. The opaque way in which all these were met undermined fiscal discipline and the integrity of the budget. Overemployment in the public sector and wage and salary increases not linked to productivity. The excessive increase in the stock of public investment projects, many being costly and unproductive. The rapid increase in the deficits of the Social Security Institutions as a result of deteriorating actuarial balance. Agricultural support policies not meeting the real needs of society. The existence of a large system of state economic enterprises system managed by interventions inconsistent with economic efficiency, and operating at high cost and low productivity. Regarding public revenues, the main problems have been the insufficient tax collection stemming from the high tax rates and narrow tax base leading to unequal distribution of the tax burden. The practice of financing budget deficits by high cost domestic borrowing has led to a rapid increase in the share of interest expenditures in the budget. In 1990, out of every 100 Turkish Liras of tax revenue, 31 Turkish Liras was spent on interest payments. In 1999, this figure reached 72 Turkish Liras. As a result, the government has become unable to allocate sufficient funds to core needs such as education, health and justice. The problems in the financial system Duties assigned to the state banks for supporting the agricultural sector and small and medium size enterprises resulted in losses which could not be covered in time by the Treasury. The state banks' financial structure was also weakened by long years of non-economic intervention in their affairs, by bad management of state banks, and by functions assigned to these banks outside their main duties. The state banks started to meet their financing requirements from the market with short maturities and high costs. On the one hand, this caused their losses progressively to increase and on the other it made them a source of instability in the financial sector. In this situation, interest rates in the markets continued at high levels. As a result, the state banks reached the point where they could scarcely carry out banking operations. While their share in bank deposits in Turkey was 40%, they only accounted for 26% of credits. The increase in the funding requirement of the public sector resulting in part from high real interest rates meant that private banks too began to channel less funds to the real sector, and instead increasingly financed the public deficits. In 1990, government domestic securities were equivalent to 10% of total assets of deposit banks. In 1999, this figure had risen to 23%. During the same period, the share of loans to the private sector in the total assets of the banks declined from 36% to 24%. Thus, the banks could not sufficiently support producers and the real economy. This environment of high inflation and uncertainty meant that savings were directed towards short-term instruments, increasing the maturity mismatch of the banks' assets and liabilities. The loss of confidence in the Turkish Lira as a consequence of the increasing debt stock as well as high and volatile inflation accelerated substitution of the Turkish Lira. The ratio of foreign exchange deposits to total deposits (including repos) rose from 25% in 1990 to 42% in 1999. Besides the shift in nearly half of bank deposits towards foreign exchange accounts, the increase in the banks' foreign borrowing also augmented the foreign exchange liabilities of banks significantly. On the other hand, the banks directed their funds into high-yield Turkish Lira denominated instruments, in particular government securities. In this situation, the banks' open foreign exchange positions increased, making the banks extremely vulnerable to currency risk. In order to achieve a sound financial sector, there is a need to ensure capital increases by the banks, to address the deficiencies in the harmonisation of legal regulations with international standards, and to accelerate efforts towards transparency in the system
Keywords: Bankacılık; Borçlar, Kamu